EFEKTIVITAS E-MODUL RELATIVITAS KHUSUS BERBASIS SAINTIFIK UNTUK MENGUKUR MINAT BELAJAR MAHASISWA PENDIDIKAN FISIKA - Amin, Ahmad; Yuneti, Armi (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
Understanding Physics concepts in the Physics Education Study Program at PGRI Silampari University is very important to support their field of expertise in understanding more complex material. Modern physics courses consist of various abstract concepts, including special relativity. The use of e-modules is very important to explain abstract material. The aim of this research is to determine students' interest in learning after implementing scientific-based special relativity e-modules in learning. The research method that will be used is a descriptive method, and data analysis that will use quantitative descriptive analysis regarding interest in learning after learning. The test subjects in this research were third semester TA students. 2024/2025 Physics education study program at PGRI Silampari University. The data collection technique uses a questionnaire, and the data collection instrument is a learning interest questionnaire sheet. The research results obtained after implementing the scientific-based special relativity e-module, the average student learning interest questionnaire score reached 73.17, with a percentage value of 94%, so it can be concluded that the application of the scientific-based special relativity e-module made students' learning interest very good.